2014
DOI: 10.1371/journal.pone.0110892
|View full text |Cite
|
Sign up to set email alerts
|

Mismatch Negativity (MMN) in Freely-Moving Rats with Several Experimental Controls

Abstract: Mismatch negativity (MMN) is a scalp-recorded electrical potential that occurs in humans in response to an auditory stimulus that defies previously established patterns of regularity. MMN amplitude is reduced in people with schizophrenia. In this study, we aimed to develop a robust and replicable rat model of MMN, as a platform for a more thorough understanding of the neurobiology underlying MMN. One of the major concerns for animal models of MMN is whether the rodent brain is capable of producing a human-like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
95
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(115 citation statements)
references
References 50 publications
19
95
0
1
Order By: Relevance
“…Furthermore, similarly to MMN (Jacobsen and Schröger, 2001), differential brain responses in animals have been attributed to deviant tones as changes in the repetitiveness of a standard tone rather than as rare tones relative to the standard tone (e.g., Ruusuvirta et al, 1998;Nakamura et al, 2011;Taaseh et al, 2011;Jung et al, 2013;Shiramatsu et al, 2013;Harms et al, 2014;Malmierca et al, 2014). Together, these findings suggest that the mechanisms for automatic auditory change detection are not limited to the human brain.…”
Section: Introductionmentioning
confidence: 93%
“…Furthermore, similarly to MMN (Jacobsen and Schröger, 2001), differential brain responses in animals have been attributed to deviant tones as changes in the repetitiveness of a standard tone rather than as rare tones relative to the standard tone (e.g., Ruusuvirta et al, 1998;Nakamura et al, 2011;Taaseh et al, 2011;Jung et al, 2013;Shiramatsu et al, 2013;Harms et al, 2014;Malmierca et al, 2014). Together, these findings suggest that the mechanisms for automatic auditory change detection are not limited to the human brain.…”
Section: Introductionmentioning
confidence: 93%
“…Mismatch negativity (MMN) is another neural phenomenon reflecting underlying sensory filtering which is revealed by studying EEG responses to trains of auditory stimuli in humans (NÀÀtĂ€nen et al, 2007) and rodents (Ehrlichman et al, 2008; Harms et al, 2014; Nakamura et al, 2011; Siegel et al, 2003; Witten et al, 2014). Unlike P1 suppression, PPI and habituation, which all dampen responses to less relevant stimuli, MMN involves the pre-attentive identification of more relevant stimuli among trains of less relevant ones.…”
Section: Objective Measurement Of Sensory Processingmentioning
confidence: 99%
“…Experimental approaches which measure sensory processing are emerging as powerful translational tools in this regard. Studies using EEG, magnetoencephalography (MEG) or startle/EMG point to analogous sensory processing deficits in humans and animal models (CastrĂ©n et al, 2003; Connolly et al, 2004; Ehrlichman et al, 2008; Ethridge et al, 2016; Harms et al, 2014; Lovelace et al, 2016; Maxwell et al, 2004; Nakamura et al, 2011; Siegel et al, 2003; Umbricht et al, 2004) and have facilitated examination of underlying mechanisms of sensory disorders in rodent models relevant to ASD/FXS. Furthermore, such studies take advantage of the properties of the neural circuitry underlying basic sensory processing, which is better characterized and may be more conserved across species than neural circuitry underlying complex social and communication behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…The MMN is measured as the difference between the auditoryevoked potential elicited by a repetitive sound compared with the potential elicited by a rare, unexpected sound (larger amplitude) in electroencephalographic studies. MMN has been positioned as a potentially promising biomarker candidate for the diagnosis of pathologies such as schizophrenia (Harms et al, 2014;Nagai et al, 2013) or autism spectrum disorders, including Asperger's syndrome (e.g., O'Connor, 2012). Patients with schizophrenia exhibited a reduced ability to detect acoustic changes reflected in reduced MMN (Fisher, Grant, Smith, Borracci, Labelle, & Knott, 2012;Hong, Moran, Du, O'Donnell, & Summerfelt, 2012;Michie, 2001).…”
Section: Overviewmentioning
confidence: 99%
“…Thus, a starting point for elucidating how alterations in neurotransmission contribute to deficits in deviance detection is to employ animal models to pharmacologically isolate the role of specific modulatory substances on event-related potentials or on correlated neuronal activity. Recent studies have demonstrated that MMN-like responses occur in animal models like the rat (Harms et al, 2014;Jung et al, 2013). Likewise, neurons that exhibit a specific decrement in their response to repetitive but not to rare sounds have been characterized in animals.…”
Section: Overviewmentioning
confidence: 99%